2018
DOI: 10.1177/0022034517750109
|View full text |Cite
|
Sign up to set email alerts
|

Rare and Common Variants Conferring Risk of Tooth Agenesis

Abstract: We present association results from a large genome-wide association study of tooth agenesis (TA) as well as selective TA, including 1,944 subjects with congenitally missing teeth, excluding third molars, and 338,554 controls, all of European ancestry. We also tested the association of previously identified risk variants, for timing of tooth eruption and orofacial clefts, with TA. We report associations between TA and 9 novel risk variants. Five of these variants associate with selective TA, including a variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
0
51
0
1
Order By: Relevance
“…Additional genetic studies of both syndromic and nonsyndromic tooth agenesis have reported mutations in WNT10A as pathogenic for the condition and suggested that this gene is responsible for over 50% of the cases of tooth agenesis, with multiple variants accounting for the variable phenotypes . A recent genome‐wide study of isolated tooth agenesis also reported significant associations with two common variants in WNT10A (rs121908120; p.Phe228Ile and rs121908119; p.Cys107Ter) . These two variants have been frequently found in both syndromic and isolated tooth agenesis, and often as biallelic variants, in combinations with additional variants in WNT10A or other genes .…”
Section: Discussionmentioning
confidence: 99%
“…Additional genetic studies of both syndromic and nonsyndromic tooth agenesis have reported mutations in WNT10A as pathogenic for the condition and suggested that this gene is responsible for over 50% of the cases of tooth agenesis, with multiple variants accounting for the variable phenotypes . A recent genome‐wide study of isolated tooth agenesis also reported significant associations with two common variants in WNT10A (rs121908120; p.Phe228Ile and rs121908119; p.Cys107Ter) . These two variants have been frequently found in both syndromic and isolated tooth agenesis, and often as biallelic variants, in combinations with additional variants in WNT10A or other genes .…”
Section: Discussionmentioning
confidence: 99%
“…1 The reported incidence of tooth agenesis is 3%-10% depending on the population being studied. [2][3][4] The incidence is higher in females, and 60% of individuals exhibit unilateral tooth agenesis. 3 Third molars are the most commonly missing permanent teeth; 23% is the often-cited incidence rate.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The incidence is higher in females, and 60% of individuals exhibit unilateral tooth agenesis. 3 Third molars are the most commonly missing permanent teeth; 23% is the often-cited incidence rate. 3 The next most prevalent missing teeth are mandibular second premolars, followed by maxillary lateral incisors.…”
Section: Introductionmentioning
confidence: 99%
“…EDAR variant c.1258C>T (p.Arg420Trp) has so far been reported only in a recent Icelandic publication referring to a genome-wide association study for tooth agenesis. 11 Our protein binding assays elucidated that this variant caused a complete abrogation of the interaction between the death domains of EDAR and EDARADD. Downstream NF-κB signaling was found to be reduced.…”
Section: Discussionmentioning
confidence: 86%